A cohort study of chronic diseases for Mongolian people: Outline with baseline data of the Moncohort study. Issue 3 (September 2016) - Enkh-Oyun, Tsogzolbaatar; Davaalkham, Dambadarjaa; Kotani, Kazuhiko; Aoyama, Yasuko; Tsuboi, Satoshi; Ae, Ryusuke; Davaa, Gombojav; Angarmurun, Dayan; Khuderchuluun, Nanjid; Nakamura, Yosikazu
Abstract: Many Mongolian people suffer from non-communicable chronic diseases. In order to plan preventive strategies against such diseases, we designed a community-based prospective cohort study of chronic diseases, called the Moncohort study, in Mongolia. This is the first nationwide large-scale cohort study of chronic diseases. This paper describes the study's rationale, design and methods with baseline data. Mongolian residents aged ⩾40 years were selected nationwide from many geographic regions in 2009. Data were collected on demographics, socioeconomic status, lifestyle, and anthropometric and biochemical measurements. In total, 2280 Mongolian residents were registered in the survey. Socioeconomic, lifestyle, anthropometric and biochemical characteristics were differentiated by gender and geographical area in descriptive data. Aging, low social class, physical inactivity and infrequent fruits intake were positively associated with histories of chronic disease in men, while aging was positively associated with histories of chronic disease in women. Factors associated with chronic diseases reveal gender-oriented strategies might be needed for their prevention. Detailed prospective analyses will illustrate the impact of risk factors on chronic diseases and lead to evidence for designing programs aimed at preventing chronic diseases and related disorders in Mongolia.